Pengaruh penggunaan ekstrak daun sirih (Piper betle linn.) pada pencelupan telur tetas itik Mojosari terhadap daya tetas dan mortalitas embrio - Ilham Putra Nandhra; Edhy Sudjarwo; Adelina Ari Hamiyanti (Faculty of Animal Science, Universitas Brawijaya, 2015)
This research was carried out from October 25th to November 22th 2014 in Tani Wanita Lestari Sejahtera group at Modopuro village, Mojosari district-Mojokerto regency. The purpose of the research was to evaluate the influence of betle leaf extract in hatching eggs dyeing on the mortality and hatchability of embryos. The material of the research was 336 hatching eggs Mojosari duck owned by Mrs Suhartatik in Modopuro village. The research used experiment method by complete random scheme. The treatment consisted of four treatments and each treatment was repeated six times, so there were twenty four units of experiment. Each experiment used fourteen eggs so there were three hundred thirty six hatching eggs. The method of the treatments were P0= without dyeing, P1= Aquadest plus 10% of extract betle leaf, P2= Aquadest plus 20% of extract betle leaf, P3= Aquadest plus 30% of extract betle leaf . The variables were hatchability and mortality of the embryos. The result of the research showed that the effect of extract betle leaf was not significant (P>0,05) on hatchability. Besides the effect of 30% of extract betle leaf for dyeing process was not significant (P>0,05) on embryos mortality. The research concluded that extract betle leaf was not able to increase hatchability and was not able to decrease duck embryos mortality. It means that extract betle leaf was not effective as substitute factor in cleaning process of hatching eggs before it was entered to the hatching machine. Keywords: Hatchability, embryos mortality